2015
DOI: 10.1016/j.jand.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Energy Density Is Positively Associated with Breast Density among Young Women

Abstract: Background Breast density is an established predictor of breast cancer risk, and there is considerable interest in associations of modifiable lifestyle factors, such as diet, with breast density. Objective To determine if dietary energy density (ED) is associated with percent dense breast volume (%DBV) and absolute dense breast volume (ADBV) in young women. Design A cross-sectional analysis was conducted with women who participated in the Dietary Intervention Study in Children Follow-Up Study (DISC06). %DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…41 Furthermore, novel work from Jones et al using the Dietary Intervention Study in Children cohort demonstrated that each one-unit increase in food-only DED conferred 25.9% higher breast density. 42 Given appreciable evidence that breast density is a risk factor for breast cancer, these data, in combination with our findings, suggest that DED may influence breast cancer risk.…”
Section: Discussionsupporting
confidence: 72%
“…41 Furthermore, novel work from Jones et al using the Dietary Intervention Study in Children cohort demonstrated that each one-unit increase in food-only DED conferred 25.9% higher breast density. 42 Given appreciable evidence that breast density is a risk factor for breast cancer, these data, in combination with our findings, suggest that DED may influence breast cancer risk.…”
Section: Discussionsupporting
confidence: 72%
“…Other aspects of a high-ED diet pattern may also influence cancer risk. For example, ED was positively associated with measures of breast density among young women independent of weight status (22). This may be very important because women with a high breast density have a 4-6-fold increase in breast cancer risk (23).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its association with MD, there are previous studies that have detected a positive association between this phenotype and caloric intake [22][23][24], one of them based on the same participants of our study [22]. With respect to weight gain in adulthood, although previous studies have observed a positive relationship with MD, both in this same sample [6] and in others [7], other studies have described an inverse association [8].…”
Section: Discussionmentioning
confidence: 40%